2013
DOI: 10.1177/0146167213485444
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Boundaries and Attitudes

Abstract: Many prejudice reduction strategies involve linking the self to outgroup members. We tested the novel question of whether establishing a potent link with a single outgroup member can reduce explicit and implicit prejudice toward the outgroup as a whole. White participants completed a mock adoption procedure where they "adopted" a baby from another country. Three experiments showed that this single link fostered perceived overlap between the self and the ethnic outgroup. This overlap mediated the effect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Recent research from our lab suggests that this would not be the case. Specifically, Gulker and Monteith (2012) found that linking a member of an outgroup to the self was associated with implicit bias reduction when participants repeatedly practiced the self–other link (Experiment 2). However, merely linking an outgroup member to the self—without conditioning this link—had no effect on implicit biases (Experiment 1).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research from our lab suggests that this would not be the case. Specifically, Gulker and Monteith (2012) found that linking a member of an outgroup to the self was associated with implicit bias reduction when participants repeatedly practiced the self–other link (Experiment 2). However, merely linking an outgroup member to the self—without conditioning this link—had no effect on implicit biases (Experiment 1).…”
Section: Discussionmentioning
confidence: 99%